Different blanching methods and their application in fruits and vegetables - Tigreros, Jaime Andres; Parra Londoño, Sebastián; Martínez Girón, Jader; Ordoñez Santos, Luis Eduardo (Revista Colombiana de Investigaciones Agroindustriales, 2021)
Blanching as a pretreatment in various food transformation processes in mass consumption products has proven to be effective both to guarantee safety and to maintain or increase bioactive compounds. Fruits and vegetables have a range of nutrients, including dietary fibers, polyphenols, vitamins C, A, B, and E, carotenoids, potassium, and iron, among others. Although a food matrix is complex, the sensory and nutritional characteristics of the resulting products from the transformation of these foods can be affected by an inadequate application of blanching. The objectives of this article were to review (1) types of scalding, (2) the purposes of scalding, and (3) the evaluation of the effectiveness of the scalding process.